2013
DOI: 10.1021/ac401305f
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic Chemical Probe for Protein Structural Characterization via Ultraviolet Photodissociation Mass Spectrometry

Abstract: A chemical probe/ultraviolet photodissociation (UVPD) mass spectrometry strategy for evaluating structures of proteins and protein complexes is reported, as demonstrated for lysozyme and beta-lactoglobulin with and without bound ligands. The chemical probe, NN, incorporates a UV chromophore that endows peptides with high cross sections at 351 nm, a wavelength not absorbed by unmodified peptides. Thus, NN-modified peptides can readily be differentiated from nonmodified peptides in complex tryptic digests create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 72 publications
0
52
0
Order By: Relevance
“…Brodbelt et al reported an amine-reactive reagent (Figure 28) that incorporated a UV chromophore at 351 nm, thus allowing the ability to pinpoint and dissociate the diagnostic probe-modified peptides among complex mixtures of unmodified peptides. 61,180 …”
Section: Applications Of Ultraviolet Photodissociation For Biologimentioning
confidence: 99%
“…Brodbelt et al reported an amine-reactive reagent (Figure 28) that incorporated a UV chromophore at 351 nm, thus allowing the ability to pinpoint and dissociate the diagnostic probe-modified peptides among complex mixtures of unmodified peptides. 61,180 …”
Section: Applications Of Ultraviolet Photodissociation For Biologimentioning
confidence: 99%
“…Successful UVPD of peptides has been demonstrated using a variety of lasers, including F 2 excimer laser (157 nm, 7.9 eV per photon), 86 ArF excimer laser (193 nm, 6.4 eV per photon), 87 a femtosecond titanium sapphire laser (800 nm, 1.5 eV per photon), 88 a Nd:YAG laser (266 nm, 4.7 eV per photon 8991 or 355 nm, 3.5 eV per photon 92 ), and a XeF excimer laser (351 nm, 3.5 eV per photon). 93 (Photodissociation has also been implemented using visible photon wavelengths, such as 473 nm.) 94,95 For each wavelength, UVPD requires a suitable chromophore for absorption of photons.…”
Section: Photoactivationmentioning
confidence: 99%
“…21 The same experimental set-up also proved to be efficient in streamlining the detection of peptides tagged with a sulfo-NHS amine reactive chromophore group, which probes the accessibility of lysine residues at the protein surface. 22 Specific photodissociation was also obtained for Tyr/His-containing peptides after derivatization with diazonium chromophore groups. 23 Detection specificity is also critical when tackling protein quantification in whole proteome by targeted mass spectrometry in selected reaction monitoring mode (SRM 25 Thus, photo-SRM showed similar or even improved detection performance compared to conventional CID-SRM for the analysis of a whole plasma hydrolysate.…”
Section: Collision-induced Dissociation (Cid) Remains the Widespread mentioning
confidence: 98%